The Subplate Layers: The Superficial and Deep Subplate Can be Discriminated on 3 Tesla Human Fetal Postmortem MRI. (7th May 2020) - Pogledic, Ivana; Schwartz, Ernst; Mitter, Christian; Baltzer, Pascal; Milos, Ruxandra-Iulia; Gruber, Gerlinde Maria; Brugger, Peter C; Hainfellner, Johannes; Bettelheim, Dieter; Langs, Georg; Kasprian, Gregor; Prayer, Daniela
Abstract: The subplate (SP) is a transient structure of the human fetal brain that becomes the most prominent layer of the developing pallium during the late second trimester. It is important in the formation of thalamocortical and cortico-cortical connections. The SP is vulnerable in perinatal brain injury and may play a role in complex neurodevelopmental disorders, such as schizophrenia and autism. Nine postmortem fetal human brains (19–24 GW) were imaged on a 3 Tesla MR scanner and the T2-w images in the frontal and temporal lobes were compared, in each case, with the histological slices of the same brain. The brains were confirmed to be without any brain pathology. The purpose of this study was to demonstrate that the superficial SP (sSP) and deep SP (dSP) can be discriminated on postmortem MR images. More specifically, we aimed to clarify that the observable, thin, hyperintense layer below the cortical plate in the upper SP portion on T2-weighted MR images has an anatomical correspondence to the histologically established sSP. Therefore, the distinction between the sSP and dSP layers, using clinically available MR imaging methodology, is possible in postmortem MRI and can help in the imaging interpretation of the fetal cerebral layers.